Clinical and anamnestic characteristics of patients depending on left ventricular ejection fraction: results of a register study - P. G. Parfenov; A. V. Yurkina; D. P. Golubovskaya; S. Y. Shuster; E. V. Dren; Y. I. Guselnikova; N. B. Lebedeva; T. B. Pecherina (Бюллетень сибирской медицины, 2024)
Aim. To study the clinical and anamnestic features of patients followed up in the Center for Chronic Heart Failure at the Regional Vascular Center according to the data of the corresponding register.Materials and methods. The study included data of 802 patients included in the Kuzbass Register of Patients Followed up at the Center for Chronic Heart Failure from 2020 to 2022. The median follow-up was 1.6 ± 0.7 years. Results. According to the present register, men dominated in the gender profile of patients with chronic heart failure – 612 (76.3%) participants (p < 0.001). The largest group of subjects was represented by patients with a low left ventricular ejection fraction (less than 40%) – 546 people. This category was also characterized by a more severe functional class of chronic heart failure (New York Heart Association); patients with functional class III– IV chronic heart failure prevailed (p < 0.001). The most common comorbidities revealed were chronic kidney disease (glomerular filtration rate of less than 60 ml / min / 1.73 m2 according to the CKD-EPI equation) – 614 (76.5%) patients and obesity (body mass index of more than 30 kg / m2) – 334 (41.6%) patients. Type 2 diabetes mellitus was reported in 193 (24%) patients. The analysis of the etiology of chronic heart failure showed that the main causes of heart failure in the groups with low and intermediate left ventricular ejection fraction were coronary heart disease and combined causes, whereas in the group with preserved left ventricular ejection fraction, the disease resulted from coronary heart disease and arrhythmogenic causes. Conclusion. Assessing the clinical and anamnestic features of patients with heart failure, it can be said that these people are mainly male, retired, with coronary heart disease, low left ventricular ejection fraction, and a comorbidity, mainly chronic kidney disease, diabetes mellitus, and obesity.